Molding materials for motors
Patent Information
- Application Number
- KR1020240062337
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-05-13
- Publication Date
- 2026-09-02
- Estimated Expiration
- 2044-05-13
Smart Images

Figure 112024051437303-PAT00001 
Figure 112024051437303-PAT00002 
Figure 112024051437303-PAT00003
Abstract
Description
Technology Field
[0001] The present invention relates to a molding material for a motor and a vehicle part molded using the same. Background Technology
[0002] Recently, epoxy resin compositions have been widely used as molding materials for automotive parts; for example, they can be used to fix permanent magnets to the rotor core of electric vehicle (EV) motors. These epoxy resin compositions serve to adjust the spacing so that the magnets are positioned at uniform intervals within the rotor and to fix the magnets so that they do not detach. Various studies are being conducted to improve the physical properties of such epoxy resin compositions for motors; for example, Japanese Patent Publication No. Hei 7-53792 discloses an epoxy composition for fixing magnets.
[0003] EV drive motors operate by converting electrical energy into kinetic energy; however, energy losses occur during the conversion process involving coils, stators, rotors, and magnets, and these losses manifest as heat. If an electric motor is operated in an environment with temperatures higher than the optimal temperature for its components due to this generated heat, core losses, mechanical losses, and copper losses may occur within the motor. Furthermore, prolonged operation at high temperatures can affect the characteristics of the permanent magnets and windings within the motor, potentially leading to a degradation of motor performance. Accordingly, there is a need for the development of molding materials with excellent heat resistance. The problem to be solved
[0004] The present invention provides a molding material for motors having excellent heat resistance. In addition, the present invention provides a vehicle part molded using the said molding material. means of solving the problem
[0005] The present invention provides a molding material for a motor manufactured by curing a molding material composition comprising an epoxy resin, a curing agent, a filler, and a morpholine-based compound containing sulfur within the molecule, wherein the reduction rate of flexural strength at a high temperature (295°C, 24 hrs, 5 cycles) relative to flexural strength at room temperature (25°C) is less than 50%. Effects of the invention
[0006] The present invention provides a motor molding material with excellent heat resistance. The motor molding material of the present invention can be applied as a molding material for vehicle parts, and, for example, can be used to fix a permanent magnet to the rotor of a vehicle motor. The motor molding material of the present invention has excellent heat resistance, so it can minimize motor losses due to heat, and thus can achieve stable motor performance and increase motor efficiency even when applied to EV drive motors that require high rotational speed and applied current. Specific details for implementing the invention
[0007] The present invention will be described in detail below. However, the scope of the present invention is not limited solely to the description below, and each component may be modified in various ways or selectively combined as needed. Accordingly, it should be understood that the invention includes all modifications, equivalents, and substitutions that fall within the spirit and technical scope of the present invention.
[0008] As used herein, “viscosity” is measured by conventional methods known in the art, for example, using a Brookfield viscometer. “Softening point” is measured by conventional methods known in the art, for example, using a Mettler Toledo Dropping Point system calorimetry DP70. “Particle size (D 50)” is measured by conventional methods known in the relevant technical field, and can be measured, for example, by laser light scattering (LLS).
[0010] Molding material for motors
[0011] The motor molding material of the present invention is manufactured by curing a molding material composition comprising an epoxy resin, a curing agent, a filler, and a morpholine-based compound containing sulfur within the molecule, and the motor molding material has a reduction rate of less than 50% in flexural strength at high temperature (295°C, 24 hrs, 5 cycles) compared to flexural strength at room temperature (25°C). By controlling the reduction rate of flexural strength at high temperature of the molding material to less than 50%, the present invention can maintain high strength and fixing power even when exposed to high temperature and high-speed rotation environments. Therefore, when the motor molding material of the present invention is used to fix permanent magnets to the rotor of a vehicle motor, the permanent magnets within the rotor slots can be stably fixed, thereby enabling stable motor performance and increasing the driving efficiency of the motor.
[0013] Epoxy resin
[0014] In the present invention, the epoxy resin is used as the main resin and, by reacting with a curing agent and curing to form a three-dimensional network structure, can impart the property of strong and rigid adhesion to a substrate, particularly a metal material such as a permanent magnet, and heat resistance.
[0015] As the above epoxy resin, epoxy resins commonly used in the relevant technical field may be used, for example, those containing two or more epoxy groups in their molecular structure may be used. Non-limiting examples of available epoxy resins include bisphenol A type epoxy resin, alicyclic epoxy resin, cresol novolak type epoxy resin, dicyclopentadiene type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, naphthalene type epoxy resin, anthracene type epoxy resin, tetramethylbiphenyl type epoxy resin, phenol novolak type epoxy resin, bisphenol A novolak type epoxy resin, bisphenol S novolak type epoxy resin, biphenyl novolak type epoxy resin, naphthol novolak type epoxy resin, naphthol phenol coaxial novolak type epoxy resin, naphthol cresol coaxial novolak type epoxy resin, aromatic hydrocarbon formaldehyde resin modified phenol resin type epoxy resin, triphenylmethane type epoxy resin, tetraphenyl ethane type epoxy resin, dicyclopentadiene type epoxy resin, dicyclopentadiene phenol addition type epoxy resin, biphenyl type epoxy resin, naphthol aralkyl type epoxy resin. There are non-condensing cyclic polycyclic epoxy resins, bisphenol fluorene modified epoxy, etc., and one or more of these may be included.
[0016] For example, the above epoxy resin may include a mixture of two types of epoxy resins and may include a dicyclopentadiene (DCPD) type epoxy resin containing an intramolecular benzene structure, such as a phenol polymer with 3a,4,7,7a-tetrahydro-4,7-methano-1H-indene, glycidyl ether or a mixture thereof, to impart heat resistance; and a phenol aralkyl type epoxy resin, such as a polymer with 1,1'-biphenyl and phenol, glycidyl ether or a mixture thereof.
[0017] The above epoxy resin may be used having an epoxy equivalent (EEW) of 100 to 400 g / eq, for example, 200 to 300 g / eq, a viscosity (150 °C) of 0.01 to 5 Pa·s, for example, 0.05 to 3 Pa·s, and a softening point of 40 to 85 °C, for example, 50 to 75 °C. If the epoxy equivalent of the above epoxy resin is less than the aforementioned range, the curing density may increase and moisture resistance reliability may be inferior, and if it exceeds the aforementioned range, the curability may be inferior. If the viscosity is below the aforementioned range, excessive leakage of the epoxy molding material may occur during molding, and if it exceeds the aforementioned range, flowability may be reduced, resulting in incomplete filling during molding. If the softening point is below the aforementioned range, excessive leakage of the epoxy molding material may occur during molding, and if it exceeds the aforementioned range, flowability may be reduced, resulting in incomplete filling during molding.
[0018] Based on the total weight of the molding material composition, the content of the epoxy resin may be 0.5 to 20 weight%, for example, 1 to 15 weight%. If the content of the epoxy resin is less than the aforementioned range, adhesion, flowability, and moldability may be reduced, and if it exceeds the aforementioned range, the reliability of the molding material may be poor due to increased moisture absorption, and strength may be reduced due to a relative decrease in the filler content.
[0020] hardener
[0021] The molding material composition according to the present invention includes a curing agent. The curing agent reacts with the epoxy resin to promote the curing of the composition and improves adhesion.
[0022] As the above curing agent, a curing agent known in the art for curing with an epoxy resin may be used, and for example, the above curing agent may be a phenolic compound having two or more phenolic hydroxyl groups in one molecule. For example, the above curing agent may include one or more selected from the group consisting of phenol novolak resin, cresol novolak resin, phenol aralkyl resin, and polyfunctional phenolic compounds. For example, the above curing agent may include a phenol polymer with 1,4-bis(methoxymethyl)benzene.
[0023] The above-mentioned curing agent may be used having a hydroxyl group equivalent of 100 to 250 g / eq, for example, 160 to 180 g / eq, a viscosity (25 ℃) of 0.1 to 2.5 poise, for example, 1 to 1.5 poise, and a softening point of 40 to 90 ℃, for example, 55 to 75 ℃. If the hydroxyl group equivalent of the above-mentioned curing agent is below the aforementioned range, the reliability of moisture resistance may be inferior, and if it exceeds the aforementioned range, the curability may be inferior. If the viscosity is below the aforementioned range, the curability and moldability may be reduced, and if it exceeds the aforementioned range, reliability may be poor and the hardness of the cured product may be reduced. If the softening point is below the aforementioned range, the strength of the cured product may be reduced, and if it exceeds the aforementioned range, moldability may be reduced.
[0024] Based on the total weight of the molding material composition, the content of the curing agent may be 1 to 20 weight%, for example, 1 to 10 weight%. If the content of the curing agent is less than the aforementioned range, the curability and moldability may be reduced, and if it exceeds the aforementioned range, the reliability of the molding material may be poor and the strength may be reduced due to increased moisture absorption.
[0026] filler
[0027] The molding material composition according to the present invention includes a filler. The filler serves to improve the strength and flowability of the molding material composition.
[0028] The above filler may be any commonly used in the relevant technical field without limitation, and for example, inorganic fillers such as silica, silica nitride, alumina, aluminum nitride, and boron nitride may be used, and these may be used individually or in combination of two or more types. The shape of the above filler is not particularly limited, and both angular and spherical shapes may be used.
[0029] The sieve residue (75 μm cut) of the above filler is 0.2% or less, for example, 0.01 to 0.1%, and the particle size (D 50 ) can be 1 to 40 μm, for example 10 to 30 μm.
[0030] Based on the total weight of the molding material composition, the content of the filler may be 60 to 93 weight%, for example, 70 to 90 weight%. If the content of the filler is less than the aforementioned range, the amount of moisture absorbed in the cured product of the molding material composition increases, which may reduce the reliability of the molding material, and if it exceeds the aforementioned range, the fluidity decreases, which may result in poor moldability.
[0032] Morpholine compounds
[0033] The molding material composition according to the present invention comprises a morpholine-based compound. The morpholine-based compound has a ring structure, which facilitates bonding with other molecules and can provide stability in chemical reactions. Therefore, the morpholine-based compound can provide an excellent adhesion-enhancing effect.
[0034] The molding material composition of the present invention can further improve the adhesive strength of the molding material composition by using a morpholine-based compound. Therefore, when the molding material composition according to the present invention is applied as a molding material for vehicle parts, for example, for fixing a permanent magnet to the rotor of a motor, stable motor performance can be achieved by stably fixing the permanent magnet even when exposed to high temperature and high-speed rotation environments.
[0035] The above-mentioned morpholine compound includes a morpholine compound containing sulfur within the molecule. Since the inclusion of sulfur allows for the formation of stronger bonds with other atoms, using a morpholine compound containing sulfur can provide a superior adhesion-enhancing effect. The above-mentioned sulfur-containing morpholine compound may include 4,4'-Dithiobismorpholine, morpholine, 4-(methylsulfonyl)-, 4-morpholinesulfonamide, etc. The aforementioned compounds may be used alone or in a mixture of two or more types.
[0036] Based on the total weight of the molding material composition, the content of the morpholine-based compound may be 0.005 to 1 weight%, for example, 0.01 to 0.5 weight%. If the content of the morpholine-based compound is less than the aforementioned range, the adhesive strength may not be sufficiently improved, and if it exceeds the aforementioned range, reliability may be reduced or fluidity may be reduced due to the influence on the curing reaction.
[0038] Adhesion promoter
[0039] The molding material composition according to the present invention may further include an adhesion promoter.
[0040] The above adhesion promoter may include a triazine-based compound, an imidazole-based compound, or a mixture thereof. When the above triazine-based compound or the above imidazole-based compound is included, excellent adhesion and oil resistance properties can be provided to the molding material composition. Therefore, when the molding material composition according to the present invention is applied as a molding material for vehicle parts, for example, for fixing a permanent magnet to the rotor of a motor, stable motor performance can be achieved by preventing the permanent magnet from detaching in an oil environment.
[0041] The above triazine-based compounds may include one or more selected from the group consisting of 1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2,4-diamino-6(2'-methylimidazolyl-(1'))-ethyl-s-triazine, and 2,4-diamino-6(2'-undecylimidazolyl-(1'))-ethyl-s-triazine.
[0042] The above imidazole-based compounds may include one or more selected from the group consisting of 6-[2-(2-methyl-1H-imidazole-1-yl)ethyl]-1,3,5-triazine-2,4-diamine, 2-methylimidazole, and 2-undecylimidazole.
[0043] In addition, the adhesion promoter may further include adhesion promoters commonly used in the relevant technical field in addition to the aforementioned compounds. As the adhesion promoter, epoxy silanes, amino silanes, mercapto silanes, acryl silanes, vinyl silanes, etc. may be used, and for example, N-[3-(trimethoxysilyl)propyl]benzenamine, (3-mercaptopropyl)trimethoxysilane, etc. may be used.
[0044] Based on the total weight of the molding material composition for motors, the content of the adhesion promoter may be 0.01 to 5 weight%, for example, 0.01 to 1 weight%. If the content of the adhesion promoter is less than the aforementioned range, the adhesion strength and oil resistance may not be sufficiently improved, and if it exceeds the aforementioned range, the filling ability may be reduced.
[0046] additives
[0047] The molding material composition according to the present invention may further include additives commonly used in the relevant technical field, such as release agents, colorants, catalysts, and flame retardants, as needed.
[0048] The release agent is intended to improve the release properties between the epoxy molding material and the external mold, and may use long-chain fatty acids, metal salts of long-chain fatty acids, paraffin wax, carnauba wax, polyethylene wax, silicone oil (e.g., modified epoxy-type silicone oil, double-terminal amine-modified silicone oil, etc.). The coloring agent is intended to impart color to the molding material composition, and may use carbon black, Bengala, etc. In addition, it may further include additives such as catalysts (e.g., triphenylphosphine, 5-methyl-2-phenylimidazole-4-methanol, etc.) to improve curing speed, workability, glass transition temperature, etc., and flame retardants (e.g., hexaphenoxycyclotriphosphazene, metal hydroxides, etc.) to impart flame retardancy.
[0049] The above additives may be added within a content range known in the relevant technical field, and for example, may be included in an amount of 0.01 to 10 weight% each with respect to the total weight of the molding material composition, but are not limited thereto.
[0051] Vehicle Parts
[0052] The present invention provides a vehicle part molded using the aforementioned molding material. For example, the aforementioned molding material can be used to fix and seal components within a vehicle part that require excellent vibration resistance, heat resistance, dimensional stability, and deformation resistance.
[0053] For example, a permanent magnet can be inserted into a void space formed within the rotor of a motor, and the molding material composition of the present invention can be filled between the void space and the permanent magnet to fix the permanent magnet within the rotor. The molding material according to the present invention has excellent heat resistance, so the permanent magnet can be stably fixed even when the motor is exposed to a high temperature and high-speed rotation environment, and stable motor performance can be achieved.
[0055] The present invention will be explained in more detail below through examples. However, the following examples are intended only to aid in understanding the present invention and do not imply that the scope of the present invention is limited to these examples in any way.
[0057] [Experimental Example 1-11]
[0058] Molding material compositions for each experimental example were prepared by mixing each component according to Tables 1 and 2 below. Using the molding material compositions of each experimental example, the high-temperature strength of the molding material was measured by the following method, and the results are listed in Tables 1 and 2 below.
[0060] Preparation of molding material specimens
[0061] Molding material specimens (length 128 mm * thickness 6.0 mm * width 12.8 mm) for evaluating flexural strength were prepared using the molding material composition of each experimental example.
[0063] Flexural strength
[0064] One cycle was defined as leaving the molding material specimen of each experimental example in a chamber (295 ℃) for 24 hours, and the flexural strength for each cycle was measured using a universal testing machine. The cycle was repeated and the flexural strength was measured until the flexural strength became 1.5 kgf / mm² or less or until the commercially available material was cut. Ref. is the flexural strength before leaving in the high-temperature chamber.
[0066]
[0067]
[0069] Epoxy resin 1: Dicyclopentadiene (DCPD) type epoxy resin (Phenol polymer with 3a,4,7,7a-tetrahydro-4,7-methano-1H-indene, glycidyl ether, Cas No. 119345-05-0, EEW 259 g / eq, viscosity (150 ℃) 0.05 Pa·s)
[0070] Epoxy resin 2: Phenol aralkyl-type epoxy resin (Formaldehyde, polymer with 1,1'-biphenyl and phenol, glycidyl ether, EEW 274 g / eq, viscosity (150 ℃) 0.01 Pa·s)
[0071] Epoxy resin 3: Ortho-cresol novolak type epoxy resin (EEW 208 g / eq, viscosity (150 ℃) 0.28 Pa·s)
[0072] Epoxy resin 4: Bisphenol A type epoxy resin (EEW 191 g / eq, viscosity (150 ℃) 0.002 Pa·s)
[0073] Hardener: Phenol polymer with 1,4-bis(methoxymethyl)benzene(Cas No. 26834-02-6)
[0074] Filler: Silica (D 50 22 µm)
[0075] Morpholine compounds: 4,4'-Dithiobismorpholine
[0076] Silane 1: N-[3-(Trimethoxysilyl)propyl]benzenamine
[0077] Silane 2: 3-Mercaptopropyltrimethoxysilane
[0078] Wax: Fatty acids, montan-wax, ethylene esters
[0079] Catalyst: Triphenylphosphine, 5-Methyl-2-phenylimidazole-4-methanol
[0080] Flame retardant: Hexaphenoxycyclotriphosphazene
[0081] Coloring agent: Carbon black
[0083] [Physical Property Evaluation]
[0084] The physical properties of the molding material compositions prepared in each experimental example were measured as follows, and the results are shown in Table 3 below.
[0086] Spiral flow
[0087] After molding the molding material composition prepared according to each experimental example using a spiral flow mold in a heat transfer molding machine (pressure 70 kg / ㎠, temperature 175 ℃, curing time 120 sec), the flowability of the manufactured product was measured.
[0089] Gel time
[0090] A small amount of the molding material composition prepared according to each experimental example was spread widely and evenly on a gel timer, and the gelation time of the product was measured (temperature 175 ℃).
[0092] adhesion
[0093] After molding the molding material composition of each experimental example into a cylindrical shape with a diameter of 5.5 mm on a copper (Cu) specimen (under the same conditions as the flowability measurement conditions), the adhesion strength was measured using a Die shear tester.
[0095] withstand voltage
[0096] After the aforementioned flexural strength test, a dielectric strength test was performed on the molding material specimens that had measured values up to 5 cycles. A dielectric strength tester device (8526, TSURUGA ELECTRIC) was set to short-circuit the electric current when the leakage current was 0.3 mA or more, electrodes were connected to the front and back of each specimen based on the thickness plane, and an AC voltage of 5 kV was applied for 30 seconds. If the leakage current generated while the AC voltage of 5 kV was applied was less than 0.3 mA, it was evaluated as pass, and if a short circuit occurred due to a leakage current of 0.3 mA or more, it was evaluated as fail.
[0098]
[0100] As shown in Table 3 above, the molding material compositions of Experimental Examples 1-4 according to the present invention exhibited excellent physical properties across all measured items. On the other hand, the molding material compositions of Experimental Examples 5-11, in which the rate of decrease in flexural strength at high temperature (295 ℃, 24 hrs, 5 cycles) relative to the flexural strength at room temperature (25 ℃) fell outside the scope of the present invention, exhibited generally inferior physical properties compared to the molding material compositions of Experimental Examples 1-4.
Claims
Claim 1 A molding material for a motor manufactured by curing a molding material composition comprising an epoxy resin, a curing agent, a filler, and a morpholine-based compound containing sulfur within the molecule, wherein the morpholine-based compound comprises one or more selected from the group consisting of 4,4'-dithiobismorpholine; morpholine, 4-(methylsulfonyl)-; and 4-morpholinesulfonamide, and the reduction rate of flexural strength at high temperature (295 ℃, 24 hrs, 5 cycles) relative to flexural strength at room temperature (25 ℃) is less than 50%. Claim 2 A molding material for a motor according to claim 1, wherein the epoxy resin comprises a dicyclopentadiene (DCPD) type epoxy resin, a phenol aralkyl type epoxy resin, or a mixture thereof, the epoxy equivalent (EEW) of the epoxy resin is 100 to 400 g / eq, the viscosity (150 ℃) is 0.01 to 5 Pa·s, and the softening point is 40 to 85 ℃, the hydroxyl equivalent of the curing agent is 100 to 250 g / eq, the viscosity (25 ℃) is 0.5 to 2.5 poise, and the softening point is 40 to 90 ℃. Claim 3 delete Claim 4 A molding material for a motor according to claim 1, comprising, based on the total weight of the molding material composition, 0.5 to 20 weight% of the epoxy resin, 1 to 20 weight% of the curing agent, 60 to 93 weight% of the filler, and 0.005 to 1 weight% of the morpholine-based compound. Claim 5 A vehicle part molded using a molding material according to any one of paragraphs 1, 2 and 4.
Citation Information
Patent Citations
Phenol resin and thermosetting resin composition
KR1020130101474A